2012
DOI: 10.21273/hortsci.47.10.1472
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of an Expansin Gene from Chimonanthus praecox Flowers and Its Expression in Flowers Treated with Ethephon or 1-Methylcyclopropene

Abstract: Expansins are extracellular proteins that are involved in cell wall modifications such as cell wall disassembly, cell separation, and cell expansion. Little is known about expansin gene expression during flower development of wintersweet (Chimonanthus praecox). In the present study, an expansin gene, CpEXP1, was isolated from the wintersweet flower cDNA library through random sequencing; this gene encodes a putative protein of 257 amino acids with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 34 publications
(30 reference statements)
0
23
0
Order By: Relevance
“…In wintersweet, however, previous research detected no obvious production of ethylene from the flowers during flower development (Sheng et al, 1999). On the other hand, it has been reported that ethephon treatment of wintersweet cut flowers can accelerate the process of flower opening (Ma et al, 2012). We previously measured ethylene production of wintersweet flowers at different stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wintersweet, however, previous research detected no obvious production of ethylene from the flowers during flower development (Sheng et al, 1999). On the other hand, it has been reported that ethephon treatment of wintersweet cut flowers can accelerate the process of flower opening (Ma et al, 2012). We previously measured ethylene production of wintersweet flowers at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…In wintersweet, the role of exogenous ethylene in cut flower senescence is still unclear since conflicting results have been reported in the past (Ma et al, 2012;Sheng et al, 1999). The cytokinin 6-BA has been reported to be involved in the postharvest management of cut wintersweet flowers (Guo and He, 2004).…”
mentioning
confidence: 99%
“…Therefore, we screened the DEGs which may be involved in the cell wall metabolism under different temperatures. EXP and XTH are involved in cell expansion, loosening and rearranging the cell wall bers in growing tissues [8], which are up-regulated during oral open process in sandersonia [28], Mirabilis jalapa [29], petunia [9], carnation [30], and wintersweet [10]. In cucumber, EXPs consist of four sub families: α-EXP, β-EXP, EXP-like A and EXP-like B and were rst discovered to loosen cell walls in pH dependent manner [31].…”
Section: Identi Cation Of Degs Involved In the Cell Wall Metabolismmentioning
confidence: 99%
“…Among them, EXP and XTH particularly participate in disrupting the non-covalent bonds between the cellulose micro brils and the cross-linking glycans of the cell wall to increase the cell-wall creep rate, while pectinase and endo-1,4β-D-glucanase can degrade the cell wall [9]. In wintersweet (Chimonanthus praecox), the expressions of EXP genes increase during ower opening [10]. The developing petals of carnation show high activities of cellulase and pectin esterase [11].…”
mentioning
confidence: 99%
“…A PrimeScript RT Reagent Kit with gDNA Eraser (TaKaRa Bio) was used to reverse transcribe equal amounts of DNA-free RNA (5 mg) from different tissues into cDNA. Real-time polymerase chain reaction (RT-PCR) was carried out according to Ma et al (2012). The relative transcript abundance was calculated with the genes for tubulin and actin (Sui et al 2012).…”
Section: Real-time Polymerase Chain Reaction Assessmentmentioning
confidence: 99%